1994
DOI: 10.1213/00000539-199403000-00011
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Propofol and Thiopental for Rapid Anesthesia Induction in Infants

Abstract: We compared the hemodynamic response to laryngoscopy and intubation, as well as emergence and recovery times, when propofol or thiopental were used for rapid intravenous induction of anesthesia in 59 infants undergoing repair of inguinal hernia. An intravenous catheter was inserted under N2O analgesia and atropine 0.01 mg/kg was administered to all patients. Subsequent induction with propofol (3 mg/kg), thiopental (5 mg/kg), or halothane (2%) was followed with succinylcholine (2 mg/kg) and tracheal intubation.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0
1

Year Published

1997
1997
2017
2017

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 0 publications
1
24
0
1
Order By: Relevance
“…In 1994, Schrum et al . compared propofol 3 mg·kg –1 , thiopentone 5 mg·kg –1 and halothane 2% as induction agents in two age groups: 1–6 months and 7–12 months (58). The infants receiving propofol showed a lesser hypertensive response during intubation than those receiving thiopentone or halothane and in the younger age group the time to awake extubation from anaesthesia was halved; 5.5 ± 2.5 vs. 10.3 ± 1.4 min.…”
Section: Intravenous Induction Agentsmentioning
confidence: 99%
“…In 1994, Schrum et al . compared propofol 3 mg·kg –1 , thiopentone 5 mg·kg –1 and halothane 2% as induction agents in two age groups: 1–6 months and 7–12 months (58). The infants receiving propofol showed a lesser hypertensive response during intubation than those receiving thiopentone or halothane and in the younger age group the time to awake extubation from anaesthesia was halved; 5.5 ± 2.5 vs. 10.3 ± 1.4 min.…”
Section: Intravenous Induction Agentsmentioning
confidence: 99%
“…anaesthetic agent which is now used routinely in paediatric anaesthesia. 1 Spontaneous movement is one of the side effects observed during induction of anaesthesia with 1% propofol. 2 It was demonstrated that increasing the loading dose from 3 to 5 mg kg 91 resulted in a significant decrease in these movements.…”
mentioning
confidence: 99%
“…Also baroreceptor reflex control of HR may be depressed by propofol [15]. The possible development of severe hypotension is the limiting factor with the use of propofol although Schrumet al [21] demonstrated that it was transient in healthy, normovolemic children. Topical laryngeal spraying of lidocaine as suggested by Abouleishet al [22] can be used as an adjunct to the technique of tracheal intubation without muscle relaxant for further improving the intubating score with no effects on hemodynamics.…”
Section: Discussionmentioning
confidence: 99%